HUBUNGAN ANTARA LAYANAN BIMBINGAN DI SEKOLAH DAN BIMBINGAN ORANGTUA DENGAN PRESTASI BELAJAR SISWA SMP - GHUFRON, M. (2011)
This research is meant to know the relationship between the guidance service at school and parent guidance with the learning achievement of Junior High School Student. The used technique of sample is cluster sampling technique. The samples in this research are two classes with number of used samples as many as 69 students. The technique to collect the data used guidance service scale at school, parent guidance and learning achievement. While the technique to analyze the data used multiplied regression analysis. Based on the result of data analysis is obtained F coefficient correlation value as follow (F = 6,514; p>0,05). This show that the relationship between guidance learning at school and parent guidance whit the achievement of Junior High School Student is significantly approved. Then from the determination coefficient (adjuster R square) is known 0,165. This show that the influence of the guidance service student as much as 16,5% while the rest is as much as 83,5%. It derived from the influence of factors and other variables outside of guidance service at school and parents guidance. Next, from examined variables that guidance service at school have correlation to the learning achievement showed with the r value = 0,324; p value = 0,007<0,05. it means that there is significant correlation between parent service and the learning achievement. So it shows that getting better of the guidance service at school and parent guidance, the higher the achievement of the learning student.